Solve for x
x=\frac{1}{10}=0.1
Graph
Share
Copied to clipboard
\left(2x-1\right)\left(3x+5\right)+3x\left(4x^{2}+9\right)=\left(4x^{2}-1\right)\left(x+\frac{3}{2}\right)-\frac{8}{3}\left(-3\right)xx^{2}
Variable x cannot be equal to any of the values -\frac{1}{2},0,\frac{1}{2} since division by zero is not defined. Multiply both sides of the equation by 3x\left(2x-1\right)\left(2x+1\right), the least common multiple of 6x^{2}+3x,4x^{2}-1,3x,3,1-4x^{2}.
6x^{2}+7x-5+3x\left(4x^{2}+9\right)=\left(4x^{2}-1\right)\left(x+\frac{3}{2}\right)-\frac{8}{3}\left(-3\right)xx^{2}
Use the distributive property to multiply 2x-1 by 3x+5 and combine like terms.
6x^{2}+7x-5+12x^{3}+27x=\left(4x^{2}-1\right)\left(x+\frac{3}{2}\right)-\frac{8}{3}\left(-3\right)xx^{2}
Use the distributive property to multiply 3x by 4x^{2}+9.
6x^{2}+34x-5+12x^{3}=\left(4x^{2}-1\right)\left(x+\frac{3}{2}\right)-\frac{8}{3}\left(-3\right)xx^{2}
Combine 7x and 27x to get 34x.
6x^{2}+34x-5+12x^{3}=\left(4x^{2}-1\right)\left(x+\frac{3}{2}\right)-\frac{8}{3}\left(-3\right)x^{3}
To multiply powers of the same base, add their exponents. Add 1 and 2 to get 3.
6x^{2}+34x-5+12x^{3}=4x^{3}+6x^{2}-x-\frac{3}{2}-\frac{8}{3}\left(-3\right)x^{3}
Use the distributive property to multiply 4x^{2}-1 by x+\frac{3}{2}.
6x^{2}+34x-5+12x^{3}=4x^{3}+6x^{2}-x-\frac{3}{2}-\left(-8x^{3}\right)
Multiply \frac{8}{3} and -3 to get -8.
6x^{2}+34x-5+12x^{3}=4x^{3}+6x^{2}-x-\frac{3}{2}+8x^{3}
The opposite of -8x^{3} is 8x^{3}.
6x^{2}+34x-5+12x^{3}=12x^{3}+6x^{2}-x-\frac{3}{2}
Combine 4x^{3} and 8x^{3} to get 12x^{3}.
6x^{2}+34x-5+12x^{3}-12x^{3}=6x^{2}-x-\frac{3}{2}
Subtract 12x^{3} from both sides.
6x^{2}+34x-5=6x^{2}-x-\frac{3}{2}
Combine 12x^{3} and -12x^{3} to get 0.
6x^{2}+34x-5-6x^{2}=-x-\frac{3}{2}
Subtract 6x^{2} from both sides.
34x-5=-x-\frac{3}{2}
Combine 6x^{2} and -6x^{2} to get 0.
34x-5+x=-\frac{3}{2}
Add x to both sides.
35x-5=-\frac{3}{2}
Combine 34x and x to get 35x.
35x=-\frac{3}{2}+5
Add 5 to both sides.
35x=\frac{7}{2}
Add -\frac{3}{2} and 5 to get \frac{7}{2}.
x=\frac{\frac{7}{2}}{35}
Divide both sides by 35.
x=\frac{7}{2\times 35}
Express \frac{\frac{7}{2}}{35} as a single fraction.
x=\frac{7}{70}
Multiply 2 and 35 to get 70.
x=\frac{1}{10}
Reduce the fraction \frac{7}{70} to lowest terms by extracting and canceling out 7.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}